Business acceptance of information and communication technologies: an study of the service sector - Ortega, Blanca Hernández (2007)
The aim of this paper is to analyse the level of development reached by some Information and Communication Technologies (ICT) such as web pages, e-mail, EDI, and business management software in the business world. To this end, we have concentrated on the business behaviour of the service sector. Nevertheless, the technological development demanded changes depending on the activity of the firm, so the mediator effect of the industry has been tested in the process of innovation acceptance. Our results show the technology acceptance process is influenced by the perception of both the usefulness and the ease of use of innovations. Moreover, the industry effect mediates the technological behaviour of a firm; meanwhile, if a firm performs a "traditional activity", there are fewer incentives to implement the innovation.